Cycling to Work. An Analysis of the Practice of Utility Cycling. - Rérat, Patrick (Springer, 2021)
This book presents a thorough discussion of utility cycling, cycling in the urban environment, and everyday mobility. It is based on large survey answered by 14,000 participants in the bike to work action in Switzerland, and quantifies the various dimensions of utility cycling. It proposes an innovative theoretical framework to analyse and understand the various dimensions of the uses of bikes and their diversity. It addresses the factors that motivate commuters to get on their bike, and highlights the barriers to this practice between deficient infrastructures and lack of legitimacy. This research makes a diagnosis and discusses the way to develop this sustainable mode of transportation. By combining quantitative results in the form of tables, figures, and maps, and including qualitative results in the form of quotations from survey participants, this book provides a thorough and enjoyable read. It will be of interest to researchers, policy makers, advanced students in the field of urban planning, social sciences, and transportation.
Keywords: Fahrradverkehr; Berufsverkehr; Pendlerverkehr; Arbeitsweg; Fahrradnutzung; Befragung; Verkehrsraum